Pemanfaatan Algoritma ID3 sebagai Prediktor Kelulusan Mahasiswa AMIK Harapan Bangsa Surakarta - Istiawan, Ismail; Purbianto, Eko (Jurnal Media Infotama, 2019)
Student graduation is one of the assessments in the accreditation of study programs and institutions. The high rate of student graduation on time is directly proportional to the accreditation score. Therefore, each university tries its best to make its students graduate on time. Several strategies were finally implemented by universities, such as holding meetings with the Academic Advisors of each class so that communication occurred which could ultimately provide solutions if potential students were detected who did not graduate on time. This research tries another approach to predict students who have the potential not to graduate on time. Computational calculations taking into account pre-existing data are an interesting topic to discuss. The ID3 algorithm has the ability to create a decision tree regarding a problem. This algorithm was used in this research and the results showed that the first factor that needs to be considered in graduating students at AMIK Harapan Bangsa Surakarta is gender. Men have a higher pass percentage than women with a percentage of 60% versus 40%. This can be a concern for AMIK Harapan Bangsa Surakarta towards final year students to detect as early as possible the potential for students not graduating on time.